STRATEGIES FOR HANDLING PROBLEMATIC ATM COMPLAINTS IN INCREASING CUSTOMER SATISFACTION AT PT. BANK MUAMALAT INDONESIA, Tbk KC PADANGSIDIMPUAN - sannita sannita; darwis harahap; sulaiman efendi; husni husni (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This study aims to find out how PT. BMI, Tbk KC Padangsidimpuan implemented a strategy for handling troubled ATM complaints in increasing customer satisfaction. The discussion of this study relates to Islamic Banking. With handling of ATM complaints, it will be able to prevent a crisis, because banks can deal with problems more quickly and recognize the initial symptoms of a crisis by evaluating ATM complaints that are problematic that can harm banks. The method used is descriptive qualitative. Data collection techniques used were interviews, observation, and documentation. Researchers see that there are two factors that cause complaints of problematic ATMs, namely: this internal factor originates from the bank's internal, namely system that is experiencing problems, so it cannot serve customer needs in conducting a transaction. In addition, human resources are less skilled, causing customers to experience complaints, and external factors stem from the behavior of customers who do not understand how to use bank facilities, one of which is not being able to use an ATM card, as well as customers who are impatient, impatient. This makes these customers tend to commit careless actions, which causes the ATM card to be blocked, the customer's account can be debited, the ATM card to be swallowed, the ATM card to be damaged or the wrong transfer can no longer be used.